Aging Versus Postmenopausal Osteoporosis: Bone Composition and Maturation Kinetics at Actively‐Forming Trabecular Surfaces of Female Subjects Aged 1 to 84 Years. (23rd September 2015) - Paschalis, Eleftherios P; Fratzl, Peter; Gamsjaeger, Sonja; Hassler, Norbert; Brozek, Wolfgang; Eriksen, Erik F; Rauch, Frank; Glorieux, Francis H; Shane, Elizabeth; Dempster, David; Cohen, Adi; Recker, Robert; et al.
ABSTRACT: Bone strength depends on the amount of bone, typically expressed as bone mineral density (BMD), determined by dual‐energy X‐ray absorptiometry (DXA), and on bone quality. Bone quality is a multifactorial entity including bone structural and material compositional properties. The purpose of the present study was to examine whether bone material composition properties at actively‐forming trabecular bone surfaces in health are dependent on subject age, and to contrast them with postmenopausal osteoporosis patients. To achieve this, we analyzed by Raman microspectroscopy iliac crest biopsy samples from healthy subjects aged 1.5 to 45.7 years, paired biopsy samples from females before and immediately after menopause aged 46.7 to 53.6 years, and biopsy samples from placebo‐treated postmenopausal osteoporotic patients aged 66 to 84 years. The monitored parameters were as follows: the mineral/matrix ratio; the mineral maturity/crystallinity (MMC); nanoporosity; the glycosaminoglycan (GAG) content; the lipid content; and the pyridinoline (Pyd) content. The results indicate that these bone quality parameters in healthy, actively‐forming trabecular bone surfaces are dependent on subject age at constant tissue age, suggesting that with advancing age the kinetics of maturation (either accumulation, or posttranslational modifications, or both) change. For most parameters, the extrapolation of models fitted to the individual age dependence of bone in healthy individuals was in rough agreement with their values in postmenopausal osteoporotic patients, except for MMC, lipid, and Pyd content. Among these three, Pyd content showed the greatest deviation between healthy aging and disease, highlighting its potential to be used as a discriminating factor. © 2015 American Society for Bone and Mineral Research.